Perturbative coherence in field theory - Aldrovandi, R. [UNESP]; Kraenkel, Roberto André [UNESP] (American Institute of Physics (AIP), 1989)
The basic field equations of a field theory are not always derivable from a Lagrangian. Lagrangian theories are perturbatively coherent, in the sense that they have well-defined vertices. Non-Lagrangian theories may be coherent or not. Coherent theories are, in principle, quantizable by perturbative methods. The general condition for a theory to have well-defined vertices is given. © 1989 American Institute of Physics.